Analisis Pengaruh Strategi Promosi dan Kualitas Produk Terhadap Keputusan Pembelian Pada PT Nulab Pharmaceutical Indonesia - Rakhmat; Sri Waluya (Mulia Pratama, 2021)
Competition in the business world is very tight, tight business competition can also be seen on the demand side for pharmacy goods. Company leaders will direct all efforts to win the competition in purchasing decisions through effective promotion strategies and good product quality. The purpose of this study was to determine the effect or how much influence the variable promotion strategy and product quality had on purchasing decisions at PT Nulab Pharmaceutical Indonesia. The method used in this study is a quantitative method, data collection techniques used by distributing questionnaires and library data. The sample of this research is the consumers at PT Nulab Pharmaceutical Indonesia totaling 50 people with random sampling method. The analytical method used is multiple linear regression. The results of data processing using SPSS version 23 found that the adjusted R square was 57.6%. That is, the variables of promotion strategy and product quality can explain the purchasing decision variables by 57.6%. The difference is influenced by other variables that are not used in this study. The results of this study conclude that partially the promotion strategy variable has no significant effect on purchasing decisions. In contrast to the product quality variables that have a significant effect on purchasing decisions at PT Nulab Pharmaceutical Indonesia simultaneously, promotional strategies and product quality affect purchasing decisions.